Impact of cosmetic products on epiphora and ocular health in female patients – a cross-sectional study - Asra Warees; Afreen Abbas; Ilma Muqeem; Sahab Kausar; Samra Nazli; Afifa Khalique; Mohd Faizan; Mohd Faraz; Kashif Abbas; Mudassir Alam (Ophthalmology, 2026)
Purpose This study evaluates the effect of cosmetic use on ocular health and the frequency of epiphora symptoms in female patients. Method This cross-sectional study included 206 female patients who visited the Department of Ophthalmology at J.N. Medical College and Hospital, AMU, Aligarh, Uttar Pradesh, India. Data were collected using a proforma, which consisted of age, gender, occupation, address, patient’s history, nature, and duration of epiphora. All patients underwent regurgitation on pressure over the lacrimal sac (ROPLAS) test and lacrimal syringing. The analysis was performed using RStudio version 4.3.3 and Python version Jupyter Notebook. Results The chi-square test of independence was conducted to examine the association between cosmetic use and ROPLAS – chi-square statistic (χ²): 8.33 with degree of freedom (df):1 and p-value = 0.0039. Although cosmetic use and the type of discharge (watery vs. mucous) revealed (χ²): 8.641 with (df):1 and p-value 0.0033. Patients who use cosmetics appear more likely to report watery discharge compared to non-users. Similarly, for cosmetic use and tearing pattern (occasionally vs. continuous) shown – (χ²): 11.2043 with (df):1 and p-value 0.0008, which is a highly significant result. However, there is no statistically significant association between cosmetic use and the other six symptoms, including pain, burning, blurred vision, redness, gritty sensation, and itching. Conclusions Statistical analysis revealed that cosmetic use does not significantly aggravate epiphora severity or associated inflammatory symptoms, but it does influence the pattern and nature of tearing, which suggest the functional and irritation rather than obstructive mechanism.